2018
DOI: 10.6118/jmm.2018.24.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Effect of Herbal Medicines and Isoflavones on the Treatment of Cognitive Function

Abstract: ObjectivesThe current overview aimed to present the effect of herbal medicines on cognitive function among menopausal women.MethodsTwo separate authors performed systematic search of the 3 databases of (the MEDLINE Scopus and the Cochrane Central Register Trials) from inception to January 2018. Methodological quality of each study was assessed using the AMSTAR.ResultsAccording to 2 reviews, soy seems to be effective in enhancing summary cognitive function and visual memory. The effect of isoflavones on cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…First, a recent meta-analysis reported no significant benefit of the Mediterranean diet, whose supplying of polyphenol is about 1g/day [49], on incident cognitive impairment [73]. In addition, an overview of the effect of soy isoflavones concluded that their effects on cognition may be limited and influenced by several factors related to individual features, type of treatment, and the plant itself [74]. Similarly, a meta-analysis of 21 clinical trials indicated that the treatment of MCI patients with Ginkgo biloba extract brought inconsistent results on the cognitive endpoint [75].…”
Section: Polyphenol Effects On Neurocognitive Functionsmentioning
confidence: 99%
“…First, a recent meta-analysis reported no significant benefit of the Mediterranean diet, whose supplying of polyphenol is about 1g/day [49], on incident cognitive impairment [73]. In addition, an overview of the effect of soy isoflavones concluded that their effects on cognition may be limited and influenced by several factors related to individual features, type of treatment, and the plant itself [74]. Similarly, a meta-analysis of 21 clinical trials indicated that the treatment of MCI patients with Ginkgo biloba extract brought inconsistent results on the cognitive endpoint [75].…”
Section: Polyphenol Effects On Neurocognitive Functionsmentioning
confidence: 99%
“…The association with probiotic was also studied for symptoms of genitourinary syndrome of menopause, but results were not satisfactory [69]. Isoflavones exert a limited beneficial effect on cognition, as increased choline acetyltransferase and brain-derived neurotrophic factor in the hippocampus and frontal cortex [70]. However, this effect may be modified by age, gender, ethnicity, menopausal status, and length of treatment [70].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…Isoflavones exert a limited beneficial effect on cognition, as increased choline acetyltransferase and brain-derived neurotrophic factor in the hippocampus and frontal cortex [70]. However, this effect may be modified by age, gender, ethnicity, menopausal status, and length of treatment [70]. The effects on bone metabolism are interesting due to a significant decrease in bone resorption process, especially if associated with HRT [26].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…The product's ability to reduce vasomotor symptoms may be predominantly associated with soy isoflavones and their ability to act as lower affinity lower, potency phytoestrogens, operating primarily as a selective modulator of the β-estrogen receptor [45]. In fact, despite the disparity among the authors regarding the effects of phytoestrogens on menopausal symptoms, several clinical trials have reported that soy isoflavones mitigate vasomotor symptoms [46], though with limited or no effects on cognition and other menopause-related symptoms [47]. Currently, isoflavones represent one of the most popular and safest alternative therapies to support menopausal complaints, although some contradictory results have been published in clinical studies [29,48].…”
Section: Discussionmentioning
confidence: 99%